The effectiveness of internet-based acceptance and commitment therapy on acceptance of illness, emotion regulation, symptom severity reduction, and symptoms interference with function in patients with breast cancer - Sara Mirzaei; Reza Bagherian-Sararoudi; Mohammad Hasan Davazdah Emami; Razieh Izadi; Mohammad Reza Sharbafchi (BMC Psychiatry)
Abstract Background The aim of this study was to investigate the effectiveness of internet based acceptance and commitment therapy on acceptance of illness, emotion regulation and reducing the severity and interference of symptoms with function of patients with breast cancer. Methods The research design was semi-experimental and of the type of randomized clinical trial, with a control group and random allocation. For this purpose, 36 patients with breast cancer were selected as available sampling. At first, eligible patients referring to Maxa Center in Isfahan were given an informed consent form and relevant checklists and questionnaires (baseline assessment), then the patients were randomly assigned to one of the two groups and the experimental group received ACT in the form of group video calls during 10 sessions of 60 min, and the control group received the education and support program in the form of group video calls. Finally, after finishing the sessions using the specified tools, the post-test and 12 weeks later follow-up of both groups were done electronically. In order to test the hypotheses, the data were analyzed using the analysis of variance with one-way multivariate Repeated measure test. Results The results showed that although the acceptance rate of the illness over time was higher in the ACT group than in the control group, the effectiveness of the Internet based ACT on this variable was not statistically significant. Online ACT over time reduces the difficulty in emotion regulation and reduces the severity of symptoms in breast cancer patients. The symptoms whose severity was significantly reduced in the experimental group mainly included the psychological field, which included fatigue, anxiety, and sadness of the patients. Meanwhile, the intensity of other symptoms of the patients (pain, disturbed sleep, etc.) decreased over time and due to the interaction of group and time (in both groups). It was found that only the time factor was significant for the nausea symptom. Although the improvement rate of symptom interference with function (mood, relationships, etc.) was higher in the experimental group than in the control group, and since all patients in the current trial had one or more clinically significant symptoms in the screening, so the changes in Symptomatic outcomes after a short intervention are significant. However, the effectiveness of the internet based ACT on this variable was not statistically significant. Conclusions This study contributes to the growing body of literature on the potential benefits of internet-based ACT for breast cancer patients. The findings indicate that this intervention holds promise in improving acceptance of illness, emotion regulation, reducing symptom severity, and minimizing symptoms' interference with function and warrants further investigation. Trial registration The ethics committee of the School of Medicine – Isfahan University of Medical Sciences approved the study (code: IR.MUI.MED.REC.1400.550 on 02/02/2022). Moreover, this study was registered in the Iranian Registry of Clinical Trials ( www.irct.ir ) with code No. IRCT20211107052984N1 on 02/02/2022.